PENGARUH PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP CITRA PT.PLN (PERSERO) AREA PEKANBARU BAGI MASYARAKAT KECAMATAN LIMAPULUH KOTA PEKANBARU - Rizky, Dea; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Companies that run their business in the midst of society is inseparable from the obligation to implement Corporate Social Responsibility (CSR) that can make a meaningful contribution to the community. This study attempts to provide the effect of a corporate social responsibility (CSR) conducted by PT. PLN Persero to company image.The theory tested in this study is the SR theory, while the stimulus referred to in this study is the corporate social responsibility program implemented by PT PLN (Persero), while the response comes from the public (community). The response will show whether the CSR program has an effect positive or negative image of the company. The method used in this research is descriptive quantitative. Quantitative research is research in the form of data obtained from the respondents that had been collected, processed and analyzed using statistical theory as a means of solving problems, so this method will provide certainty in decision making. Collecting data using questionnaires and documentation. Total population of as many as 8227 respondents. The sample in this study of 100 people who obtained based on the formula slovin while the sampling technique used is accidental sampling. Measurement data using a Likert scale. Data analysis techniques used in this study is a simple linear regression. The results showed sig. 0,000 obtained by measurement through SPSS version 24.0 is smaller than the probability of 0.05, thus it can be concluded that the independent variable (Corporate Social Responsibility) significantly influence the dependent variable (Corporate Image) or Ha accepted and H0 is rejected. Corporate Social Responsibility (X) has a proportion of 40.2% against the influence of Citra PT. PLN (Persero) Area Pekanbaru while the remaining 59.8% is influenced by other variables not examined in this study as the quality of human resources, corporate culture, work facilities and equipment, management systems and indormasi used, top management leadership, types and qualities, the target market, the translation of the vision and mission of the company, or the welfare of employees.